2005
DOI: 10.1111/j.0038-4941.2005.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion and Dynamic Representation in the American States: The Case of Environmental Attitudes*

Abstract: Objective. We investigate causal processes linking environmental conditions, attitudes, and policies in the American states: Is public opinion about ecology shaped by environmental conditions? Are state policymakers responsive to environmental opinions? Does public opinion respond to policy adoption? Methods. Using public opinion data from the DDB Worldwide Life Style Survey to measure aggregate state attitudes about the environment, as well as measures of water quality and policy intervention, we capture the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 46 publications
(71 reference statements)
2
82
1
Order By: Relevance
“…Younger individuals often have more concern for preserving the environment than older individuals (Dunlap et al 2000;Hunter et al 2004;Kanagy et al 1994;Xiao and Dunlap 2007;Xiao and McCright 2007). Younger individuals also express more willingness to sacrifice economic development for ensuring environmental quality (Johnson et al 2005). We expect to find that aging reduces environmental actions; although, age should have less impact than environmental quality and level of economic development.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Younger individuals often have more concern for preserving the environment than older individuals (Dunlap et al 2000;Hunter et al 2004;Kanagy et al 1994;Xiao and Dunlap 2007;Xiao and McCright 2007). Younger individuals also express more willingness to sacrifice economic development for ensuring environmental quality (Johnson et al 2005). We expect to find that aging reduces environmental actions; although, age should have less impact than environmental quality and level of economic development.…”
mentioning
confidence: 82%
“…Areas with severe environmental problems frequently have more support for taking action to solve the problems (Inglehart 1995;Johnson et al 2005;. For example, countries like Russia, Turkey, and the Czech Republic with extreme environmental problems have higher levels of concern than countries with fewer problems (Franzen 2003).…”
mentioning
confidence: 99%
“…Running (2013) used the same statistical methodology in a list of 43 nations and reported a positive and significant relation between CO2 emissions and concern for global warming. Other studies that found a positive link between objective environmental conditions and environmental concern include Anderson et al (2007), Harrris (2006, Johnson et al (2005), Newig (2004, and Schelhas and Pfeffer (2005). However, it should be noted that there may be a cleavage between local and global environmental degradation.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
“…Nor is it surprising that they would try to do so, given that public opinion can shape the political opportunity structure in which leaders operate (Green et al, 1993). At the aggregate level, public opinion can ultimately influence public policy, including environmental policy (Johnson et al, 2005). At the individual level, citizens' views regarding climate change can shape their behaviour, including voluntary actions to combat climate change and voting choices regarding referenda on government action to combat climate european political science: 11 2012 polarisation in the USA change (Bord et al, 2000;O'Connor et al, 1999).…”
Section: Party Signals and Public Opinion About Climate Changementioning
confidence: 99%